1968
DOI: 10.1038/bjc.1968.29
|View full text |Cite
|
Sign up to set email alerts
|

Nucleases and adenosine deaminase in malignant and non-malignant lesions of the human thyroid

Abstract: IN the previous paper (Ayre, Goudie and Goldberg, 1968) we compared dehydrogenase enzyme patterns in normal, hyperplastic and neoplastic human thyroid tissue. In this communication we report our findings on nucleases in the same pathological material. MATERIALS AND METHODSThe same two series of thyroid glands studied previously were investigated for nuclease activity. In the first, 56 samples of human thyroid tissue were fractionated into 3 cytoplasmic preparations-mitochondria, microsomes and supernatant. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1968
1968
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…1). This validates the comparison between normal and malignant tissues at the two pH values chosen, a useful precaution when investigating an ill-defined enzyme or group of enzymes active over a wide pH range, since mouse ascites tumours have a pH proffle for ribonuclease which differs from that of normal mouse tissues (Colter, Kuhn and Ellem, 1961), and the pH activity curve for ribonuclease in hyperplastic human thyroid tissue was not identical with that of the normal gland (Goldberg and Goudie, 1968). The existence of a proteolytic enFyme similar to the cathepsin D of beef spleen (Press, Porter and Cebra, 1960) and of rabbit spleen (Lapresle andWebb, 1960, 1962) has been demonstrated in guinea-pig intestinal mucosa (Kregar, Turk and Lebez, 1967).…”
Section: Comparison Of Two " Normal " Groupssupporting
confidence: 60%
See 1 more Smart Citation
“…1). This validates the comparison between normal and malignant tissues at the two pH values chosen, a useful precaution when investigating an ill-defined enzyme or group of enzymes active over a wide pH range, since mouse ascites tumours have a pH proffle for ribonuclease which differs from that of normal mouse tissues (Colter, Kuhn and Ellem, 1961), and the pH activity curve for ribonuclease in hyperplastic human thyroid tissue was not identical with that of the normal gland (Goldberg and Goudie, 1968). The existence of a proteolytic enFyme similar to the cathepsin D of beef spleen (Press, Porter and Cebra, 1960) and of rabbit spleen (Lapresle andWebb, 1960, 1962) has been demonstrated in guinea-pig intestinal mucosa (Kregar, Turk and Lebez, 1967).…”
Section: Comparison Of Two " Normal " Groupssupporting
confidence: 60%
“…Support for this suggestion was not forthcoming from a subsequent study of human thyroid neoplasms (Goldberg and Goudie, 1968). More recently, investigations by Sylven (1968a and b) revealed a high content of degradative lysosomal enzymes, especially cathepsin B, in the interstitial fluid of solid mouse tumour transplants, and the author speculated that cellular detachment by proteolytic enzymes may play an important role in tumour invasiveness.…”
mentioning
confidence: 99%
“…In most cases, however, biochemical studies with homogenates of experimental tumours and/or tumour bearing organs revealed an increase of acid and/or a decrease of alkaline DNase activity (7,8,13). Less consistent results were obtained with spontaneous blastomas (5).…”
Section: Discussionmentioning
confidence: 95%
“…Increased beta-2-microglobulin (B2M) expression was seen in thyroid cancer [32][33][34]. Increased enzymatic activity of ADA was seen for thyrotoxicosis, thyroid cancer, adenomas and thyroiditis [35]. Aberrant methylation patterns for serpin family B member 5 (SERPINB5) (together with TIMP3, RARB2, RASSF1, TPO and TSHR) were used to distinguish between papillary thyroid cancer (PTC) and normal thyroid tissue [36].…”
Section: Discussionmentioning
confidence: 99%